(untitled) (American Journal of Islam and Society, 2012)
The revolutions that started in Tunisia and spread to other countries in the Middle East have been dubbed the “Arab Spring.” Many countries in the Middle East have been under the thumb of an oppressive dictator. After several decades of this oppression, the people in these countries have resisted the continuance of this rule. As the smoke clears, the task of rebuilding and reforming the institutions of government is the most important task ahead for those who demanded change. The most important aspect of this change is the country’s constitution. The constitution of these countries must play the same role as the constitution in the United States. These constitutions must embody the change the reformers desire and be as inclusive as possible to be legitimate. One of the concerns of some international observers is the rise of the prominence of Islamic conservative parties. Another concern is the inclusion in the articles of the proposed new constitutions of these countries articles that declare Islam and Islamic law as the foundation of the constitutions ...